Електронейромоніторинг і хірургічна тактика за інвазії диференційованого раку щитоподібної залози до поворотного гортанного нерва - Ларін, О. С.; Черенько, С. М. (Clinical Endocrinology and Endocrine Surgery, 2008)
Authors improved the surgical treatment tactics in case of invasive forms of differentiated thyroid cancer complicated with laryngeal paresis by the way of implication of electric nerve integrity monitoring (NIM 2, Xomed, Medtronic, USA). In the case of existing-even minimal-response from the corresponding vocal fold after stimulating the nerve by low power electric current (1-2 mА) surgeon decides to remove tumor without nerve resection, as well as in case of preserving laryngeal function on preoperative laryngoscopy. Except the case with intraluminal invasion, operations on trachea or larynx should be limited by superficial (“shaving”) or “window” resection. Proposed surgical tactics allows achieving restoration of laryngeal function in 2/3 of patients not affecting oncological radicality and not increasing the rate of local relapses.